DEFISIT SOSIAL SEBAGAI PREDIKTOR GANGGUAN SPEKTRUM AUTISME - Veranita Pandia, Setiawan, Tuti Wahmurti Ari Sapiie, Herri Suhari Sastramihardja (NEURONA, 2013)
INTRODUCTION AUTISM SPECTRUM DISORDERS ASDS IS DEFINED BY DEFICITS IN THREE AREAS OF FUNCTIONING SOCIAL COMMUNICATIVE AND BEHAVIOR HOWEVER IMPAIRMENTS IN SOCIAL INTEREST SOCIAL DEFICIT IS CENTRAL TO THE DISORDER CURRENTLY ASDS PREVALENCE SEEMS TO HAVE INCREASED GREATLY THESE ESTIMATES ARE CLOSE TO 6 PER 1000HOWEVER ASDS IS DIAGNOSED INFREQUENTLY IN CHILDREN YOUNGER THAN 3 YEARS OF AGE THE DIAGNOSTIC PROCESS IS PROMPTED MOST OFTEN BY PARENTAL CONCERN ABOUT ABSENT OR DELAYED SPECCH ALTHOUGH THE SOCIAL DEFICIT ARE PRESENT IN MOST CHILDREN BY 18 MONTHS OF AGE INDEED SOCIAL DEFICIT SYMPTOMS CAN BE DETECTED EARLY THEREFORE THAT TREATMENT FOR CHILDREN AS DIAGNOSED ASD CAN BE DONE AS EARLY AS POSSIBLE IMPLICATIONS FOR STUDY INTO SOCIAL DEFICIT AS PREDICTOR IN ASDS ARE DISCUSSED